Pharmaceutical Composition of Nanotea Powder for the Prevention of Diabetic Nephropathy - Kabita; Madan, Jitender (International Journal of Psychosocial Rehabilitation, 2019)
The chronic loss of kidney function in patients with long standing poorly controlled diabetes melitus and end-stage kidney failure globally is diabetic nephrotherapy (DN) which is also called "diabetic kidney disease." Numerous shifts in the processing units of the kidneys, i.e. the nephrons, accompany this. In chronic Type 1 and Type 2 diabetes mellitus, this type of disease is seen. Various research studies have been carried out in both fundamental science as well as clinical therapy which have increased the understanding and pathophysiology of diabetic nephrotherapy (DN) and expanded the therapeutic agents for the treatemnet. The present invention was designed to provide a novel nanotea powder formulation comprising of constituents that bear different mechanism of actions for the management of diabetic mellitus and diabetic nephropathy. Nanotea powder composed of Epigallocatechingallate, Rutin and Stevioside was formulated using lyophilization (freeze drying) method following which pharmaceutical characteristics of powder were evaluated. The disease was caused by a single dose of streptozotocin (STZ) (50mg / kg, i.p) in the overnight-fasted adult wistar rats weighing 180-210 g. After 8 weeks of STZ administration, diabetic nephropathy grew. Thereafter, Diabetic rats were treated with formulated nanotea powder by oral route for 15days. An array of biochemical estimations were performed such as serum glucose level, serum albumin, serum creatinine, blood urea nitrogen, serum total cholesterol, serum high density lipoprotein (HDL) and serum triglycerides, urine albumin and urine creatinine to measure the extent of pathological damage.